Enhancing EFL Students’ Vocabulary Mastery through Canva-Based Multimodal Learning Integrated with Multicultural Content at SMP Katolik Deli Murni - Maryanti Lucciana Sitorus (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Vocabulary mastery is a fundamental component of English as a Foreign Language (EFL) learning because students’ ability to understand and use English depends strongly on their lexical knowledge. However, vocabulary instruction at the junior high school level is often dominated by memorization, translation, and textbook-based exercises that may not sufficiently support retention, motivation, creativity, and meaningful language use. This study investigated the effect of Canva-Based Multimodal Learning integrated with multicultural content on Grade VIII students’ vocabulary mastery at SMP Katolik Deli Murni. The study employed a quasi-experimental pretest-posttest control group design. The population consisted of all Grade VIII students of SMP Katolik Deli Murni, while the sample consisted of 60 students divided into an experimental class and a control class, with 30 students in each group. The experimental class was taught through Canva-based multimodal learning integrated with multicultural content, while the control class received conventional vocabulary instruction. Data were collected through vocabulary tests, student perception questionnaires, interviews, and classroom observation. The results showed that the experimental group improved from a pretest mean of 59.4 to a posttest mean of 86.7, with a gain score of 27.3. The control group improved from a pretest mean of 59.5 to a posttest mean of 75.0, with a gain score of 15.5. The independent sample t-test showed a significant difference between the groups, p < .001, with a large effect size, Cohen’s d = 1.45. Questionnaire results showed highly positive student perceptions in learning motivation, vocabulary retention, creativity development, cultural awareness, active participation, and overall satisfaction. Interview and observation findings confirmed that visual, textual, collaborative, and cultural elements made vocabulary learning more enjoyable, memorable, and meaningful. The study concludes that Canva-based multimodal learning integrated with multicultural content is an effective instructional strategy for enhancing EFL students’ vocabulary mastery and cultural awareness.